2020
DOI: 10.1002/jccs.202000103
|View full text |Cite
|
Sign up to set email alerts
|

Study of electronic effect in bifunctional catalysts for the copolymerization of CO2 and PO/CHO

Abstract: Carbon dioxide (CO 2) is an easily available renewable carbon source that can be used as a comonomer in the catalytic ring-opening polymerization of epoxides to form aliphatic polycarbonates. Herein, a series of new Salen-Co(III) bifunctional catalysts were synthesized for the first time, and they were studied to catalyze the copolymerization of CO 2 and propylene oxide (PO)/cyclohexene oxide (CHO). At the same time, the effects of reaction conditions (electronic effect, temperature, time) on catalytic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This phenomenon may be due to the weak electronic interaction between the oxygen in PO and the manganese around the cluster, resulting in a low selectivity of the catalyst for PPC/CPC. 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be due to the weak electronic interaction between the oxygen in PO and the manganese around the cluster, resulting in a low selectivity of the catalyst for PPC/CPC. 41 …”
Section: Resultsmentioning
confidence: 99%
“…interaction between the oxygen in PO and the manganese around the cluster, resulting in a low selectivity of the catalyst for PPC/CPC. 41 In order to investigate the relationship between the structure and activity of the clusters, the catalytic effect of the composite catalysts on the copolymerization of CO 2 and PO was studied using cluster I in combination with different photosensitizers. The copolymerization results show that cluster I with photosensitizer R2 containing an electron-withdrawing group exhibits higher selectivity and activity than cluster I itself.…”
Section: Copolymerization Of Co 2 and Pomentioning
confidence: 99%
“…Utilization of CO 2 as the C1 source for the production of valuable chemicals is attracting increasing interest because CO 2 is inexpensive, nontoxic, and abundant. One promising method is the copolymerization of CO 2 and epoxides, which produces polycarbonates that have found many applications in packaging, agricultural, and biomedical industries. A number of catalysts have been developed for copolymerization, including complexes of zinc, cobalt, chromium, magnesium, iron, nickel, and rare-earth metals. Among these examples, cobalt salen complexes have been reported to show good activity and selectivity (Scheme , left). Coates et al reported the first Co­(III) salen complex, which gave >99% selectivity to poly­(propylene carbonate) .…”
Section: Introductionmentioning
confidence: 99%
“…Coates et al reported the first Co­(III) salen complex, which gave >99% selectivity to poly­(propylene carbonate) . Modifications were then made to the salen ligand, including introducing quaternary ammonium moieties and Lewis base units, which resulted in cobalt-based catalysts for diverse activities.…”
Section: Introductionmentioning
confidence: 99%
“…Desirably, the process is undergone in perfectly alternating fashion; in practice, divergence from the monomers' alternations often occurs, which is attributed to the experimental conditions or catalyst design [23]. As demonstrated by the experimental studies, the catalytic activity of binary and bifunctional systems appears to be affected by the structure of both the organometallic core and the cocatalyst salt [31,34,[36][37][38][39][40][41][42][43][44][45][46][47]. These findings, along with quantum-chemical studies (of rather limited number and dedicated mostly to less-computationally challenging binary catalysts) enabled a discussion of the various mechanistic aspects of CO 2 /epoxides copolymerization that can be found in the literature concerning cobalt(III)-based catalysts [17,21,41,[48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%